Correlation between Trace Element Levels in Iraqi Breast Cancer Patients - Alhashimy, Hadeel; Shaymaa Abdulzahra Abbas (Iraqi Journal of Pharmaceutical Sciences, 2023)
Breast Cancer (BC) is the most common disease in the human body in both sex , male and female ,Trace elements (TEs) like copper (Cu); zinc (Zn) and iron (Fe) have a vital role in biological and metabolic effects including activation or inhibition of enzymatic reaction, reactive oxygen species (ROS), competition between trace elements and metal proteins for binding positions and modifications in the permeability of cellular membranes which affect on cancers events.This paper reviews measured trace elemental concentrations of cancerous and noncancerous blood sample by drawing 5 ml of venous blood from all patient and control (healthy persons) ,the serum was separated then used to measure the Zn,Cu and Fe. by using. a convenient colorimetric assay. The statistical significant association was determined, the p values is larger than 0.05 so the data considered statistically significant ,and there is a difference in the levels of trace elements (Zn, Cu and Fe) in four groups ; the median of Zn and Cu were highest in control group compared to the rest groups ,the median of Fe is highest in benign group compared to the rest groups .